Growth Hormone and Cerebral Amyloidosis - Benvenga, S.; Guarneri, F. (Hormone and Metabolic Research, 2016)
Great interest has recently been focused on a paper reporting characteristic deposits of amyloid-β protein associated with Alzheimer’s disease in brains of adults who died of Creutzfeldt-Jakob disease. As they had contracted such disease after treatment with prion-contaminated human growth hormone extracted from cadaver-derived pituitaries, the authors have suggested that interhuman transmission of Alzheimer’s disease had occurred. Our previous research led us to find that amyloid-forming peptides share amino acid sequence homology, summarized by a motif. Here, we probed the amino acid sequence of human growth hormone for such a motif, and found that 2 segments fit the motif and are potentially amyloid-forming. This finding was confirmed by Aggrescan, another well-known software for the prediction of amyloidogenic peptides. Our results, taken together with data from the literature that are missing in the aforementioned paper and associated commentaries, minimize the contagious nature of the iatrogenically-acquired coexistence of Creutzfeldt-Jakob disease and Alzheimer’s disease. In particular, the above mentioned paper misses literature data on intratumoral amyloidosis in growth hormone- and prolactin-secreting adenomas, tumors relatively frequent in adults, which are often silent. It cannot be excluded that some pituitaries used to extract growth hormone contained clinically silent microadenomas, a fraction of which containing amyloid deposits, and patients might had received a fraction of growth hormone (with or without prolactin) that already was an amyloid seed. The intrinsic amyloidogenicity of growth hormone, in the presence of contaminating prion protein (and perhaps prolactin as well) and amyloid-β contained in some cadavers’ pituitaries, may have led to the observed co-occurring of Creutzfeldt–Jakob disease and Alzheimer’s disease.
Keywords: somatotropin; amyloid; Alzheimer’s disease; bioinformatics; pituitary; microadenomas